PENERAPAN MODEL PEMBELAJARAN KOOPERATIF ACTIVE KNOWLEDGE SHARING UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON KELAS X SMAN 1 SIAK HULU - Juliana RistaMaria Lubis; Rini '; Rasmiwetti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Research on the application of cooperative learning model Active Knowledge Sharing has been conducted to improve student learning achievement on the topic Hidrokarbon at class X SMAN 1 Siak Hulu. This research is experimental research with randomized control group pretest-posttest design. The sample took in the April – Mei 2016. The sample consisted of two classes, X1 class as experimental class and X3 class as control class. Experimental class is a class that is used cooperative learning model Active Knowledge Sharing, while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic > ttable is 2,5 > 1,67 It means that the application of cooperative learning model Active Knowledge Sharing can improve student achievement on the topic Hidrokarbon at class X SMAN 1 Siak Hulu. The category of the increasing learning achievement in experiment group included into high level by the normalized score gain (N – gain) was 0.704.Keywords: cooperative learning, Active Knowledge Sharing, learning sachievement, Hidrokarbon